Implications for Drama therapy in working single-mother households in the South African context - Vilakazi, Nonkululeko (My University, 2022)
According to Sonubi (2011) black women are the lowest-earning group across elementary and managerial positions in South Africa, compared to white women, white men, and black men. There are 41 percent of black women who occupy elementary, low-paying, and less secure jobs and within this 41 percent, are single mothers who are rearing children of absent fathers. To the best of my knowledge, there is little written about the developmental effects that father absence has on children growing up in black single-mother headed households in South Africa. In addition there appears to be a paucity of literature on therapeutic interventions accessible to children reared by single-mothers. This paper explores literature related to possible developmental effects on children due to the absence of the father. This research also investigates conceptual literature on child development and drama therapy to determine whether drama therapy can be suggested as a therapeutic intervention for mitigating the psychological, behavioural, cognitive and relational developmental implications resulting from father absence. Drama therapy is proposed as a possible therapeutic intervention because of the way it engages children within their expressive frame of play. The use of drama therapy as a potential intervention is based on the strength of its ability to facilitate emotional and social support.
A research report submitted in partial fulfilment of the requirements for the degree of Master of Arts to the Faculty of Humanities, Wits School of Arts , University of the Witwatersrand, Johannesburg, 2021